1983
DOI: 10.1111/j.2044-8260.1983.tb00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of induced mood on the recall of positive, negative and neutral words

Abstract: Previous investigations have consistently found differential effects of induced moods on the accessibility of personal memories differing in hedonic tone. Findings for effects of retrieval mood on recall of verbal material have been less consistent. This study examined the effect of induced mood on the recall of previously learned personality trait words. Trait words were presented in normal mood and recall tested in elated or depressed mood. More positive words were recalled in elated than in depressed mood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
135
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(142 citation statements)
references
References 9 publications
2
135
3
Order By: Relevance
“…The results of the two experiments supported our hypothesis that mood-congruity effects (Bower, 1981;Bower et al, 1981;Bower et al, 1978;Clark & Fiske, 1982;Teasdale & Russell, 1983;Teasdale & Taylor, 1981) can be produced by activating the subject's knowledge about a mood state and its corresponding behavioral pattern. Subjects who are instructed to behave as if they were happy remembered more positively than negatively or neutrally valenced words.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The results of the two experiments supported our hypothesis that mood-congruity effects (Bower, 1981;Bower et al, 1981;Bower et al, 1978;Clark & Fiske, 1982;Teasdale & Russell, 1983;Teasdale & Taylor, 1981) can be produced by activating the subject's knowledge about a mood state and its corresponding behavioral pattern. Subjects who are instructed to behave as if they were happy remembered more positively than negatively or neutrally valenced words.…”
Section: Discussionsupporting
confidence: 75%
“…In many experimental studies the standard procedure is to start with a mood induction in subjects so that its effects on cognitive processes can be analyzed (Blaney, 1986;Bower, 1981;Bower, Gilligan, & Monteiro, 1981;Bower, Monteiro, & Gilligan, 1978;Clark & Fiske, 1982;den Uyl & Frijda, 1984;Teasdale & Russell, 1983;Teasdale & Taylor, 1981). These studies have reported mooddependent effects of two kinds: (1) Mood-state-dependent retention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Velten procedure has been widely employed and between 30 and 50 % of subjects fail to experience a measurable change in mood (Polivy & Doyle, 1980 ;Teasdale & Taylor, 1981 ;Sutherland et al 1982 ;Teasdale & Russell, 1983). Mood induction with music is effective in a greater proportion of subjects (Sutherland et al 1982 ;Clark, 1983).…”
Section: Mood Inductionmentioning
confidence: 99%
“…Studies on this topic have investigated memory for words that have affective or emotional connotation (e.g., Anisfeld & Lambert, 1966;Bousfield, 1950;Broadbent & Gregory, 1967;Cason & Lungren, 1932;Levinger & Clark, 1961;Teasdale & Russell, 1983;White, 1936). A. S. Brown (1976) has provided a catalog of published studies reporting scaled verbal material.…”
mentioning
confidence: 99%